COMPARISON BETWEEN GOVERNMENTAL AND GENERAL ACCOUNTING. - Herbert, Leo (The Accounting Review, 1948)
Abstract Accounting for governmental and institutional bodies is a means to an end and is not the end by itself. Recent criticism of the field of governmental accounting has resulted because, as so often happens in commercial accounting, heads of accounting departments think that as a result of the control vested in them, their department is the final governing body. One authority states that it believes governmental administration does not require the use of involved accounting systems, procedures, or techniques except in occasional, special situations. In general accounting it is necessary to account for all costs and to allocate those costs to revenues for a particular period to determine net income. In governmental accounting the records kept are those of revenues and expenditures, and furthermore, the cost of a building, a bridge, or equipment is just as much an expenditure as the cost of labor or supplies. Generally speaking, the revenues are allocated to expenditures in governmental accounting rather than applying costs to revenues which is found in general accounting. Profit-making ordinarily is no concern of a governmental administrator, and almost all theory regarding accounting for profits is excluded from a governmental accounting system.